1985
DOI: 10.1111/j.1365-2648.1985.tb00825.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of recovery following hysterectomy and major cardiac surgery

Abstract: Although monitoring progress is an everyday nursing activity, methods currently employed remain relatively undeveloped. In the past most studies documented physical recovery, tending to focus upon complications such as infection rates, which are quantifiable. Patients' satisfaction with progress is seldom taken into account, although it may provide a more accurate reflection of progress. In this paper, recovery following major cardiac surgery and hysterectomy performed for benign lesions are compared in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
1
10
1
Order By: Relevance
“…7 A few reports of insomnia after hysterectomy can be found in literature. 9,30 The present study showed on the contrary, that gynecological disorders, and not hysterectomy, have a negative effect on women's sleeping patterns. Pelvic pain, an irritated bladder, or soaking wet sanitary pads will disturb women's sleep.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…7 A few reports of insomnia after hysterectomy can be found in literature. 9,30 The present study showed on the contrary, that gynecological disorders, and not hysterectomy, have a negative effect on women's sleeping patterns. Pelvic pain, an irritated bladder, or soaking wet sanitary pads will disturb women's sleep.…”
Section: Discussioncontrasting
confidence: 69%
“…9,30 Furthermore, earlier onset of menopausal symptoms and presumed ovarian failure was reported in hysterectomized women compared with nonhysterectomized control women. 25,31 The present study revealed no menopausal symptoms after the operation.…”
Section: Discussionmentioning
confidence: 98%
“…An estimate for the sample size was determined on the assumption that the satisfaction rate after hysterectomy should be about 95% (Gath et al 1982; Gould & Wilson‐Barnett 1985). The alpha (type 1) value, which is the probability of detecting a significant difference when the treatments are equally effective, was set at 0.05, and the beta (type II) value, which is the probability of not detecting a significant difference when there really is a difference, was set at 0.1.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have recommended pre-operative programmes should not merely involve information provision, as is frequently the case (Wilson-Barnett and Osborne 1983, Stephenson 1988, Swindale 1989, Walsh and Ford 1989, Gould and Wilson-Barnett 1995, Waisel and Truog 1995, Knudsen 1996, Lancaster 1997, Foulger 1997, Ruuth-Setälä, et al 2000. Numerous studies have stressed the need for effective programmes of psychosocial support (Badner et al 1990, O'Rourke et al 1991, Mitchell 1994, Thomas 1995, Lindén and Engberg 1995, Stengrevics et al 1996, De Groot et al 1997b, Heikkilä et al 1998, Shuldham 1999) and many have highlighted the benefits to be gained from such programmes (Devine 1992, Kugler et al 1994b, Garden et al 1996, Klafta and Roizen 1996, Royal College of Surgeons of England and Royal…”
Section: Growth and Expansionmentioning
confidence: 99%
“…Moreover, many studies have emphasised the various aspects of psychosocial care and information provision required alongside modern surgical practices (French 1979, Reading 1982, Schoessler 1989, Yount and Schoessler 1991, Lonsdale and Hutchison 1991, Johnston et al 1992, Kratz 1993, Fareed 1994, Gould and Wilson-Barnett 1995, Goodman 1997, Motyka et al 1997, Bradshaw et al 1999, Fellowes et al 1999.…”
Section: Growth and Expansionmentioning
confidence: 99%